2000
DOI: 10.1094/phyto.2000.90.10.1068
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of Cucumber mosaic virus by Aphis gossypii Correlates with Viral Accumulation and Is Affected by the Presence of Its Satellite RNA

Abstract: Satellite RNAs (satRNAs) are associated with Cucumber mosaic virus (CMV) in tomato, most often causing severe epidemics of necrotic plants, and not associated with specific host symptoms. Laboratory studies on virus transmission by the aphid vector Aphis gossypii were performed to better understand the dynamics of field populations of CMV. The presence of satRNAs correlated with lower concentrations of virus in infected plants and with a decrease in the efficiency of transmission from satRNA-infected plants. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 38 publications
3
45
0
1
Order By: Relevance
“…No experimental data exist to underpin the functions r(x), p(x) and u(x), and these were chosen to reflect the accepted common wisdom of increasing roguing rate, increasing probability of detecting an infected cutting and decreasing reversion with increasing virus titre. The only well-studied example of the relationship between transmission rate and virus titre (Escriu et al 2000) relates to cucumber mosaic virus transmitted by A. gossypii and shows a saturating transmission rate for larger virus titres. However, note that this does not contradict our assumption of a linear relation between transmission rate and x, as x can be scaled to match the relation of Escriu et al (2000) without changing the qualitative behaviour of the other functions.…”
Section: (B) Evolving Traitmentioning
confidence: 99%
See 1 more Smart Citation
“…No experimental data exist to underpin the functions r(x), p(x) and u(x), and these were chosen to reflect the accepted common wisdom of increasing roguing rate, increasing probability of detecting an infected cutting and decreasing reversion with increasing virus titre. The only well-studied example of the relationship between transmission rate and virus titre (Escriu et al 2000) relates to cucumber mosaic virus transmitted by A. gossypii and shows a saturating transmission rate for larger virus titres. However, note that this does not contradict our assumption of a linear relation between transmission rate and x, as x can be scaled to match the relation of Escriu et al (2000) without changing the qualitative behaviour of the other functions.…”
Section: (B) Evolving Traitmentioning
confidence: 99%
“…The only well-studied example of the relationship between transmission rate and virus titre (Escriu et al 2000) relates to cucumber mosaic virus transmitted by A. gossypii and shows a saturating transmission rate for larger virus titres. However, note that this does not contradict our assumption of a linear relation between transmission rate and x, as x can be scaled to match the relation of Escriu et al (2000) without changing the qualitative behaviour of the other functions. Reduction of the roguing rate corresponds to reducing the parameter u s , and reducing the transmission rate corresponds to reducing the parameter b s .…”
Section: (B) Evolving Traitmentioning
confidence: 99%
“…Data that indicate selection of virulence in Beet curly top virus (BCTV) and Rice grassy stunt virus have been reported [38]. The evolution of virulence in populations of CMV and its satRNA depend on trade-offs between increased virulence and decreased transmissibility; consequently, not only the size, but also the evolution, of the virus population depends on the population dynamics of the aphid vectors [19,20,21]. Because of their effect on the fitness of the host plant, viruses can determine the size and/or the genetic composition of plant populations, which in turn could affect virus evolution.…”
Section: Selectionmentioning
confidence: 99%
“…Accordingly, it was shown that satRNA spreads epidemically as a parasite in the CMV population (Alonso-Prados et al, 1998). However, because satRNA depresses CMV accumulation, and the efficiency of CMV transmission by aphids correlates positively with its accumulation in source plant tissues (Betancourt et al, 2011;Escriu et al, 2000b), the efficiency of transmission of isolates supporting a satRNA may be much less than for satRNA-free isolates. This dynamic represents a trade-off between the efficient within-host multiplication of the satRNA and its betweenhost transmission, as satRNA multiplication reduces CMV transmission on which the satRNA depends for its own transmission.…”
mentioning
confidence: 99%
“…Note that from the estimates of the transmission probability by a single aphid given by Betancourt et al (2008), the expected probability of transmission of satRNA-free Fny-CMV in one passage would be 0.64 for 2 aphids/plant, and 0.98 for 8 aphids/plant, which would not explain the fast decrease of incidence in high-aphid-density passages. However, the efficiency of transmission varies non-linearly with CMV concentration in source leaves (Betancourt et al, 2011;Escriu et al, 2000b), and CMV accumulation varies among infected plants. Notably, the presence of N-satRNAs severely reduces Fny-CMV accumulation in tomato (Escriu et al, 2000a(Escriu et al, , 2003, resulting in severe decreases of transmission probability -from 0.40 to 0.11, by a single aphid (Betancourt et al, 2008) -and, therefore, single-passage transmission probabilities of 0.21 and 0.81 for 2 and 8 aphids/plant, respectively.…”
mentioning
confidence: 99%